Comparing and measuring the practice-based performance and competence of occupational therapy students between traditional and role emerging placements: a retrospective cohort study. - Thew, Miranda; Cezar da Cruz, Daniel; Thomas, Yvonne (Brazilian Journal of Occupational Therapy / Cadernos Brasileiros de Terapia Ocupacional, 2023)
Introduction: Increasingly occupational therapy programmes have complemented traditional practice placements with Role Emerging Placements (REPs) in settings with no existing occupational therapy provision. Previous research has predominantly explored the student experience of such placements with largely favorable findings. However, there is a lack of understanding regarding the professional practice-based skills students develop within REPs. Objective: To measure and compare students' competencies for occupational therapy practice developed within Role Emerging Placements (REP) to those in 'traditional' practice placements. Method: A retrospective cohort study design was used to analyze data extracted from the Competency Based Fieldwork Evaluation for Occupational Therapists (CBFE-OT) of MSc pre-registration occupational therapy UK students (n=181). Descriptive and inferential statistical analysis measured and compared student fieldwork competency scores between four placements, one of which was a Role Emerging Placement (REP). Results: Students scored significantly higher in 'Communication' and 'Professional Interactions' compared to all other practice competencies but scored significantly less well in 'Clinical Reasoning' and 'Practice Knowledge' regardless of placement model. However, in a REP, students scored significantly higher in 'Performance Management' compared to traditional placements (z=-2.222 p=0.026). Conclusion: Students can develop similar skills of competence to practise in a REP as traditional placements and may better develop leadership and time management skills. These additional skills may advantage students in developing their careers and scoping the profession.